Hippocampus experience inference for safety critical control of unknown multi-agent linear systems - Perrusquía, Adolfo; Guo, Weisi (Elsevier, 2023)
Risk mitigation is usually addressed in simulated environments for safety critical control. The migration of the final controller requires further adjustments due to the simulation assumptions and constraints. This paper presents the design of an experience inference algorithm for safety critical control of unknown multi-agent linear systems. The approach is inspired in the close relationship between three main areas of the brain cortex that enables transfer learning and decision making: the hippocampus, the neocortex, and the striatum. The hippocampus is modelled as a stable linear model that communicates to the striatum how the real-world system is expected to behave. The hippocampus model is controlled by an adaptive dynamic programming (ADP) algorithm to achieve an optimal desired performance. The neocortex and the striatum are designed simultaneously by an actor control policy algorithm that ensures experience inference to the real-world system. Experimental and simulations studies are carried out to verify the proposed approach.
Keywords: Hippocampus; Neocortex/striatum; Experience inference; Model reference; ADP; Actor algorithm; Unknown linear system; Multi-agent systems; Unbiased control policies